Amorphous Bimetallic Oxide–Graphene Hybrids as Bifunctional Oxygen Electrocatalysts for Rechargeable Zn–Air Batteries. Issue 38 (14th August 2017) - Wei, Li; Karahan, H. Enis; Zhai, Shengli; Liu, Hongwei; Chen, Xuncai; Zhou, Zheng; Lei, Yaojie; Liu, Zongwen; Chen, Yuan
Abstract : Metal oxides of earth‐abundant elements are promising electrocatalysts to overcome the sluggish oxygen evolution and oxygen reduction reaction (OER/ORR) in many electrochemical energy‐conversion devices. However, it is difficult to control their catalytic activity precisely. Here, a general three‐stage synthesis strategy is described to produce a family of hybrid materials comprising amorphous bimetallic oxide nanoparticles anchored on N‐doped reduced graphene oxide with simultaneous control of nanoparticle elemental composition, size, and crystallinity. Amorphous Fe0.5 Co0.5 O x is obtained from Prussian blue analog nanocrystals, showing excellent OER activity with a Tafel slope of 30.1 mV dec −1 and an overpotential of 257 mV for 10 mA cm −2 and superior ORR activity with a large limiting current density of −5.25 mA cm −2 at 0.6 V. A fabricated Zn–air battery delivers a specific capacity of 756 mA h gZn −1 (corresponding to an energy density of 904 W h kgZn −1 ), a peak power density of 86 mW cm −2 and can be cycled over 120 h at 10 mA cm −2 . Other two amorphous bimetallic, Ni0.4 Fe0.6 O x and Ni0.33 Co0.67 O x, are also produced to demonstrate the general applicability of this method for synthesizing binary metal oxides with controllable structures as electrocatalysts for energy conversion. Abstract : Simultaneous control of bimetallic oxide nanoparticle elemental composition, size, and crystallinity yields a high‐performance bifunctional oxygen evolution and reduction electrocatalyst for rechargeable Zn–air batteries. This method has general applicability toward various binary, tertiary, or even quadruple metal systems.